Social Media Marketing pada Perusahaan Oleh-oleh Lokal di Yogyakarta: Studi Kasus pada Instagram Bakpia Mandiri 214 - Anggi Putri Jelita; Ratna Roostika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to test and analyze social media marketing at local souvenir companies in Yogyakarta (Case Study on Instagram Bakpia Mandiri 214). Model and hypothesis testing was carried out using a sample of 40 respondents. Data was taken directly using a questionnaire with a population of consumers or followers from Bakpia Mandiri 214 Instagram. Sampling used non-probability sampling techniques. Hypothesis testing uses the Structural Equation Modeling (SEM) model which is processed using the SMART-PLS program. The variables in this research are Social Media Activity, Brand Awareness, Brand Image, E-Wom, and Commitment. These variables form the objective of the hypothesis in this research. This research provides results that Social Media Activities have a positive effect on Brand Awareness. Social Media Activities have a positive effect on Brand Image, Brand Awareness has a positive effect on E-Wom. Brand Awareness has a positive effect on Commitment. Brand Image has a positive effect on E-Wom, Brand Image has a positive effect on Commitment.